2004
DOI: 10.1007/s00247-004-1252-2
|View full text |Cite
|
Sign up to set email alerts
|

Complications of pediatric paranasal sinusitis

Abstract: Acute paranasal sinus infection in children is often diagnosed clinically without the need for radiographic confirmation. Most cases have a favorable outcome following appropriate antibiotic therapy. A small percentage of cases where symptoms and signs are persistent or severe will require emergent imaging to rule out complications related to local spread of disease intraorbitally or intracranially. A strong index of suspicion is required in such cases, and cross-sectional imaging evaluation with CT and MRI sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
2
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 22 publications
0
30
2
4
Order By: Relevance
“…Weitere in der Literatur beschriebene vital bedrohliche Komplikationen einer Sinusitis umfassen Sinusvenenthrombose, Meningitis, Enzephalitis, parenchymale Abszessbildung und zerebralen Infarkt [4]. Die in unserem Fall beobachtete milde traumatische oder kompressive Optikusneuropathie stellt eine der weniger schweren okulären Komplikationen dar.…”
Section: Diskussionunclassified
“…Weitere in der Literatur beschriebene vital bedrohliche Komplikationen einer Sinusitis umfassen Sinusvenenthrombose, Meningitis, Enzephalitis, parenchymale Abszessbildung und zerebralen Infarkt [4]. Die in unserem Fall beobachtete milde traumatische oder kompressive Optikusneuropathie stellt eine der weniger schweren okulären Komplikationen dar.…”
Section: Diskussionunclassified
“…The reason why radiologists are eager not to overlook signs of sinusitis may be due to the fact that early diagnosis and treatment are crucial to avoid intraorbital or intracranial extension. The actual diagnosis may be difficult because clinical symptoms overlap with those of non-specific upper respiratory tract (URT) infection [4, 10,11]. A review of the literature shows that recent radiological publications on this diagnostic dilemma are rare.…”
mentioning
confidence: 99%
“…Orbital complications secondary to sinusitis are mostly orbital infections and can be staged according to Chandler's classification (Chandler et al 1970) into five groups (Group I: inflammatory edema, Group II: orbital cellulitis, Group III: subperiosteal abscess, Group IV: orbital abscess, Group V: cavernous sinus thrombosis). Subperiosteal abscess is the most common intraorbital complication in the pediatric population (Reid 2004). In children, the periosteum at the medial orbital wall is loosely attached to the underlying lamina papyracea (Reid 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Subperiosteal abscess is the most common intraorbital complication in the pediatric population (Reid 2004). In children, the periosteum at the medial orbital wall is loosely attached to the underlying lamina papyracea (Reid 2004). A recent review of cases of pediatric subperiosteal abscess suggested that immediate surgical intervention is not always the best treatment option (Bedwell and Bauman 2011;Bedwell and Choi 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation